Overview of Traditional Aromatic Medicinal Plants for Diabetes in the City and Proximal area of Khemisset (Morocco) (Indian Journal of Public Health Research & Development, 2021)
According to the French Diabetes Federation, 5 million people died of diabetes in 2015. One person dies ofdiabetes every 6 seconds in the world. In developing countries, patients often resort to traditional medicineusing aromatic medicinal plants (AMPs).Some of these plants contain toxic phytochemicals. In this work, we used questionnaires distributed topatients to develop an inventory of the MPA used in the city of Khémisset and its province, geographic arealocated east of the city of Rabat (political capital of Morocco). The way of use and the used part or parts ofthe plant are determined.So, a catalog of 41 used antidiabetic plant species has been inventoried in this region. These species aresystematically grouped into 40 genera and 24 botanical families. The Brassicaceae and Fabaceae families,with four species each, are the most represented; The Asteraceae, Cucurbitaceae and Lamiaceae familieshave three species each. Olea europaea, Allium cepa, Coriandrum sativum, Caralluma europea, Citrulluscolocynthis, Tetraclinis articulata and Lupinus lotus are the most popular species. The leaves are the mostused organs (26.83%) and 43.90% of the used medicinal flora contains a significant number of toxiccompounds.
Keywords: Diabetes; Therapy; Medicinal plants; Way of use; Khemisset; Morocco.